2002
DOI: 10.1002/app.11342
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and performance of phenolic polybutadiene‐bound stabilizers

Abstract: An antioxidant derivative, 6-sulfanylhexyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoate, was synthesized and examined. With a radical initiator, the addition of this compound to pending vinyls of OH-telechelic, low molecular weight liquid polybutadiene (LBH) was performed to various degrees of conversion to form polymeric antioxidants (PAOs) in which the phenolic moiety was separated from the main chain by a spacer [OCH 2 CH 2 OSO (CH 2 ) 6 OOOCOO]. Pure, unstabilized LBH was mixed in several ratios with PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[6][7][8][9][10] The polymer include natural rubber, [11][12][13] polyolefin, [14][15][16] polybutadiene, [17][18][19] and others. 10,20,21 Podesva et al 22,23 synthesized a polymerbound antioxidant by free-radical addition reaction between a sterically hindered phenolic antioxidant with a sulfanyl group and OH-telechelic polybutadiene. The results showed that the antioxidant had better antioxidative performance and long-term persistence than the commercial antioxidant Irganox 1076.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The polymer include natural rubber, [11][12][13] polyolefin, [14][15][16] polybutadiene, [17][18][19] and others. 10,20,21 Podesva et al 22,23 synthesized a polymerbound antioxidant by free-radical addition reaction between a sterically hindered phenolic antioxidant with a sulfanyl group and OH-telechelic polybutadiene. The results showed that the antioxidant had better antioxidative performance and long-term persistence than the commercial antioxidant Irganox 1076.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low thermal stability, poor migration resistance and poor extraction resistance, the physical loss of low molecular weight antioxidant was large during polymer processing and long‐term service, which severely restricted its applications. In order to overcome the problem, macromolecular antioxidant had attracted much attention in recent years . For example, Kim synthesized several kinds of polymeric antioxidants by copolymerization or homopolymerization of functional monomers containing hindered phenol.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the problem, macromolecular antioxidant had attracted much attention in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For example, synthesized several kinds of polymeric antioxidants by copolymerization or homopolymerization of functional monomers containing hindered phenol. El-Wakil et al [9][10][11][12] studied the grafting of o-aminophenol, 1,2-phenylenediamine,1,5-diaminonaphthalene, and N-(4-aminodiphenyl methane) acrylamide onto natural rubber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pode s sva and coworkers investigated the attachment of phenolic antioxidant with a sulfanyl group to the pendent vinyls of hydroxyl terminated polybutadiene (HTPB) by free radical addition, and the results showed that antioxidant effect of the prepared antioxidant was superior to low molecular weight antioxidant due to persist in polymer matrix [27,28] . Thus, 2,2-Thiobis (4-methyl-6-tert-butylphenol) (TPH) is an important antioxidant of sterically hindered phenol.…”
mentioning
confidence: 98%